Anaphylaxis in Brazil between 2011 and 2019. Issue 9 (20th July 2022) - Tanno, Luciana Kase; Molinari, Nicolas; Annesi‐Maesano, Isabella; Demoly, Pascal; Bierrenbach, Ana Luiza
Abstract: Background: There is a lack of population‐based studies of anaphylaxis from low‐ and middle‐income countries. This hampers public health planning and investments and may influence availability of adrenaline auto‐injectors. Objective: We conducted the first national population‐based study of anaphylaxis hospitalization in Brazil. Methods: Descriptive study using routinely reported data to the Brazilian Hospital Information System for the years 2011–2019. Information available is coded based on the International Classification of Diseases (ICD)‐10 and covers main cause of hospitalization (primary cause) and any conditions contributing to it (secondary cause). Results: Over 9 years, we identified 5716 admissions due to anaphylaxis for all causes. The average hospitalization rate related to anaphylaxis was 0.71/100, 000 population per year, with a 2.4% (95% CI 1.9%, 2.9%) increase per annum over the study period. Admissions were more frequent among females (52.8%), except for cases due to insect sting. Most admissions occurred in adulthood, from 30 to 59 years (36.3%) but 13.8% in preschool children (0–4 years). There were more young children admitted for food‐related anaphylaxis, and more adults admitted for drug/iatrogenic‐related anaphylaxis. There were 334 cases (5.8% of admissions) of fatal anaphylaxis over the study period, with increased case fatality rate over time. Conclusions and Clinical Relevance: This is the first study of anaphylaxis hospital admissions using nation‐wide data from a low‐ or middle‐income country. Hospital admissions and fatalities from anaphylaxis in Brazil appear to be increasing. Abstract : Data from the Brazilian Hospital Information System, which accounts for approximately 75%–80% of hospitalizations in Brazil, were analysed for 2011‐2019. A stepwise approach was used to identify hospitalizations for anaphylaxis, using ICD‐10 codes. This first study on anaphylaxis hospital admissions using Brazilian national data showed an average rate of 0.71 admissions per 100, 000 population per year, with a 2.4% increase per annum between 2011 and 2019. More young children were admitted for food‐related anaphylaxis and more adults for drug‐related anaphylaxis. Fatal anaphylaxis occurred in 5.8% of admissions, and fatalities appeared to increase over time. [Correction added on 10 August 2022, after first online publication: The Graphical Abstract text was incorrect and has been updated in this version.]